PENGARUH DEMOKRASI TERHADAP PERUBAHAN MEKANISME PEMILIHAN KEPALA DAERAH OLEH DEWAN PERWAKILAN RAKYAT DAERAH (DPRD) - Puspa Rani, Nabella (Universitas Riau, 2014)
The hallmark of a state of democracy is the implementation of the general election.The system was based on the implementation of the elections of the form ofdemocracy there , either directly or indirectly (representatives) .The state of theunity of the republic of indonesia as an archipelago is one of the state an adherentof the popular sovereignty, namely democracy pancasila .So that all the activitiesof the state and government shall not contravene with the values of philosophypancasila and still consider the constitution state that is the Undang Undang Dasar1945.Keywords: Democracy, Local Election, Pancasila